2022
DOI: 10.1371/journal.pone.0268541
|View full text |Cite
|
Sign up to set email alerts
|

Aquaporin 4 is not present in normal porcine and human lamina cribrosa

Abstract: Aquaporin 4 is absent from astrocytes in the rodent optic nerve head, despite high expression in the retina and myelinated optic nerve. The purpose of this study was to quantify regional aquaporin channel expression in astrocytes of the porcine and human mouse optic nerve (ON). Ocular tissue sections were immunolabeled for aquaporins 1(AQP1), 4(AQP4), and 9(AQP9), myelin basic protein (MBP), glial fibrillary acidic protein (GFAP) and alpha-dystroglycan (αDG) for their presence in retina, lamina, myelin transit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 55 publications
3
6
0
Order By: Relevance
“…While the MON must withstand some motion in the orbit, it is not subjected to the stress generated by IOP. We have recently demonstrated that mouse UON astrocytes and astrocytes of all mammalian ONH lack aquaporin expression [27], and differential Aqp4 expression was also observed in the current study. It is now widely recognized that astrocyte gene expression varies substantially in the many regions of the central nervous system [28,29].…”
Section: Discussionsupporting
confidence: 84%
“…While the MON must withstand some motion in the orbit, it is not subjected to the stress generated by IOP. We have recently demonstrated that mouse UON astrocytes and astrocytes of all mammalian ONH lack aquaporin expression [27], and differential Aqp4 expression was also observed in the current study. It is now widely recognized that astrocyte gene expression varies substantially in the many regions of the central nervous system [28,29].…”
Section: Discussionsupporting
confidence: 84%
“…While the MON must withstand some motion in the orbit, it is not subjected to the stress generated by IOP. We have recently demonstrated that UON astrocytes and astrocytes of all mammalian ONH lack aquaporin expression [27], and differential Aqp4 expression was also observed in the current study (data not shown). It is now widely recognized that astrocyte genetic expression varies substantially in the many regions of the central nervous system [28,29].…”
Section: Discussionsupporting
confidence: 83%
“…Connexin43(CX43) [ 21 ] also expresses in astrocytes and can be a specific marker for identification of astrocytes. Aquaporin 4 (AQP4) [ 22 ] is absent from astrocytes in the rodent optic nerve head. F4/80 and OSP [ 23 ] label microglia and oligodendrocytes, respectively.…”
Section: Resultsmentioning
confidence: 99%